Fabrication of Organolead Iodide Perovskite Solar Cells with Niobium-doped Titanium Dioxide as Compact Layer - Thuat, Nguyen Tran; Thoa, Bui Bao; Tran, Nguyen Bao; Tu, Nguyen Minh; Minh, Nguyen Ngoc; Huong, Hoang Ngoc Lam; Trang, Pham Thu; Van, Phan Vu Thi; Tu, Truong Thanh; Linh, Dang Tuan (Communications in Physics, 2017)
Organometal halide perovskite materials have shown high potential as light absorbers for photovoltaic applications. In this work, perovskite planar solar cells were fabricated on corning substrates with the structure as follows: the first layer made of tantalum-doped tin oxide as transparent contact material, followed by sputtering niobium-doped titanium oxide as the compact electron transport layer; covered with perovskite CH3NH3PbI3 as the light harvester by combination between spin-coating and dipping methods; CuSCN was evaporated as the hole transport layer; the final thin Al/Ag electrodes were deposited. This configuration is shortly described as Al/TTO/NTO/CH3NH3PbI3/CuSCN/Ag. Such heterojunctions are expected to be suitable for the development of efficient hybrid solar cells. The fabricated cells were measured under the air mass 1.5 illumination condition, showed the rectification effect and exhibited a power conversion efficiency of 0.007%, with a open circuit voltage of 53.2 mV, a short circuit current of 0.36 mA/cm2, and a form factor of 37%. The power conversion efficiency will be further optimized in near future